2021
DOI: 10.17159/2309-8775/2021/v63n1a3
|View full text |Cite
|
Sign up to set email alerts
|

Reliability performance of bridges designed according to TMH7 NA load model

Abstract: The current code of practice for the design of highway bridges in South Africa is called Technical Methods for Highways 7 (TMH7). It was first published in 1981 and is largely based on the loading provisions of the BS5400. The purpose of this study is to carry out an investigation into the reliability performance of new highway bridges designed according to TMH7. Past studies have identified deficiencies in the traffic load model. A case study considering isolated traffic load effects and sagging moment on a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…A CoV of V R = 0.175 is used here for the structural resistance, which includes provision for model uncertainty. Lenner et al (2021) and Van der Spuy (2020) concluded that the load effect of traffic loading in SA is best modelled by a censored generalised extreme value distribution. In previous research by Steenbergen et al (2018) and Fischer et al (2019), however, it was found that the combined load effect of permanent (normal distribution) and variable loading (extreme value distribution) was well represented by a lognormal distribution for V R , V S < 0.3.…”
Section: Target Reliability In South Africa Through Cost Optimisationmentioning
confidence: 99%
See 1 more Smart Citation
“…A CoV of V R = 0.175 is used here for the structural resistance, which includes provision for model uncertainty. Lenner et al (2021) and Van der Spuy (2020) concluded that the load effect of traffic loading in SA is best modelled by a censored generalised extreme value distribution. In previous research by Steenbergen et al (2018) and Fischer et al (2019), however, it was found that the combined load effect of permanent (normal distribution) and variable loading (extreme value distribution) was well represented by a lognormal distribution for V R , V S < 0.3.…”
Section: Target Reliability In South Africa Through Cost Optimisationmentioning
confidence: 99%
“…This is due to the fact that at the time of compilation of TMH7, circa 1980, the use of reliability as a basis for structural design was still in its infancy. Recent research (Lenner et al 2021;Van der Spuy 2020) indicates that the currently achieved levels of reliability from TMH7 may not be in line with those from SANS 10160-1. Irrespective, TMH7 is now outdated and needs considerable revision or replacement.…”
Section: Introductionmentioning
confidence: 99%